2018
DOI: 10.1080/19476337.2017.1389989
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of antioxidant activity of Morchella esculenta protein hydrolysate by optimized glycosylation reaction

Abstract: Morchella protein hydrolysate (MPH) is produced from an edible and medicinal fungus, Morchella esculenta (L.), and exhibits antioxidant activity. In order to further improve the antioxidant activity of MPH, glycosylation of MPH was conducted by applying response surface methodology via the Maillard reaction (MR). Optimum glycosylation conditions were confirmed as: xylose/MPH mass ratio of 3.7:1, pH 11.80, and reaction time 60 min. The glycosylation of MPH under these optimized conditions was characterized by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…These fi ndings are similar to the earlier study which reported the antioxidative activities of rice dreg protein hydrolysate [Zhang et al, 2016]. The protective effect may be due to the wide range of antioxidant activities MPH and G-MPH possess and the roles they play as H 2 O 2 and free radical scavengers, which have been confi rmed in our previous studies [Zhang et al, 2018b].…”
Section: Mph and G-mph Inhibited H 2 O 2 -Induced Ros Generation And supporting
confidence: 92%
See 2 more Smart Citations
“…These fi ndings are similar to the earlier study which reported the antioxidative activities of rice dreg protein hydrolysate [Zhang et al, 2016]. The protective effect may be due to the wide range of antioxidant activities MPH and G-MPH possess and the roles they play as H 2 O 2 and free radical scavengers, which have been confi rmed in our previous studies [Zhang et al, 2018b].…”
Section: Mph and G-mph Inhibited H 2 O 2 -Induced Ros Generation And supporting
confidence: 92%
“…MPH and G-MPH were prepared based on our previous report [Zhang et al, 2018b]. Briefl y, the Morchella protein was hydrolyzed using papain at an enzyme/protein ratio of 2% in a shaking water bath at 45°C for 3 h, at pH 6.0.…”
Section: Preparation Of Mph and G-mphmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of a sugar is related to its structure and form in solution. Xylose has less steric hindrance and a greater proportion of its active form; these factors could promote the reaction with amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…MPH was prepared according to our previously described method (Zhang, Wu, Fan, Li, & Sun, ). Morchella protein was extracted by alkali extraction and acid precipitation procedure from mycelium obtained by liquid fermentation.…”
Section: Methodsmentioning
confidence: 99%